Crystal plasticity and cohesion model coupling hydrogen induced cracking simulation method based on test
By coupling crystal plasticity and cohesion models and combining multi-source experimental data, a polycrystalline model was constructed, which solved the accuracy problem of simulating hydrogen-induced cracking in metallic materials, realized the hydrogen cracking process, provided high-precision hydrogen-induced cracking analysis, and ensured the safety of energy facilities.
Patent Information
- Application Number
- CN202511218259.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-12-09
AI Technical Summary
Existing methods for simulating hydrogen-induced cracking in metallic materials are insufficient to accurately describe the entire process of crack nucleation and propagation, leading to errors in hydrogen-induced cracking failure analysis and affecting the safety of energy facilities.
A hybrid model based on experimental crystal plasticity and cohesion was adopted. A polycrystalline model was constructed by testing the mechanical properties of metallic materials under hydrogen calorific value, fracture toughness, electron backscatter diffraction microscopic characterization, and polycrystalline equipment. The hydrogen-induced cracking behavior was then analyzed by combining the results with finite element simulation.
This study achieved high-precision simulation of the microscopic mechanism of hydrogen-induced cracking in metallic materials under hydrogen-environment conditions, reducing model uncertainty and ensuring energy security and reliability.
Smart Images

Figure CN121093692A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of finite element numerical simulation technology for hydrogen-induced crack propagation in metallic materials, and particularly to an experimentally based method for simulating hydrogen-induced cracking by coupling a crystal plasticity and cohesion model. Background Technology
[0002] Fossil fuels still account for a large proportion of the ever-increasing energy demand, and their extensive use has caused enormous damage to the environment and climate. Global warming, caused by carbon dioxide emissions from fossil fuel consumption, is the most prominent issue. Hydrogen energy, as a clean, efficient, and versatile energy carrier, serves as a bridge between traditional fossil fuels and renewable energy. Developing hydrogen energy can effectively optimize the energy structure, reduce the consumption of traditional fossil fuels, and promote the transformation and upgrading of the energy structure. Building a clean, low-carbon, safe, and efficient modern energy system with hydrogen energy as a key element is an important foundation for implementing the new energy security strategy and advancing the energy revolution, and is of great significance for energy transformation and development in the new era.
[0003] However, hydrogen molecules are small and highly diffusive, easily adsorbing and dissociating on the surface of metallic materials to form hydrogen atoms. These atoms then penetrate into the material's interior and accumulate at defects, ultimately leading to hydrogen-induced cracking failure. The brittle fracture behavior caused by hydrogen involves multiple scales, generally originating at the microscale from defects such as microcracks and micropores. Once a crack forms, it propagates rapidly, reaching near the speed of sound in metals, eventually causing brittle fracture failure at the macroscale. Due to scale limitations, hydrogen-induced cracking exhibits a hysteresis loop, and the macroscopic properties of metallic materials depend on their microstructural characteristics. Understanding the evolution of microscopic damage helps to further refine the macro- and microscopic failure mechanisms of hydrogen-induced cracking in pipeline steel. Observational experiments are one of the effective means of detecting microcracks within metals, but modern microscopic characterization techniques cannot capture the entire process of crack nucleation and propagation. Existing methods for simulating cracks in metallic materials mainly rely on numerical simulations to obtain constitutive model parameters, inevitably leading to errors compared to real-world conditions. Therefore, in order to ensure the safe and effective operation of energy facilities and to further understand the mechanism of hydrogen-induced crack propagation in metals, it is essential to conduct experimental research and analysis on the hydrogen-induced cracking behavior of metallic materials. Summary of the Invention
[0004] To address the aforementioned technical problems, the present invention aims to provide an experimentally based simulation method for hydrogen-induced cracking coupled with a crystal plasticity and cohesion model, used to simulate and analyze the microscopic mechanism of hydrogen-induced cracking behavior in metallic materials in hydrogen-exposed environments.
[0005] This invention is achieved using the following technical solution: a hydrogen-induced cracking simulation method based on an experimental crystal plasticity and cohesive force model, comprising the following steps: S1: Conduct hydrogen-charged mechanical property tests on metallic materials to obtain true stress-strain curves of metallic materials under hydrogen-exposed environments; S2: Conduct hydrogen-charged fracture toughness tests on metallic materials to obtain the stress intensity factor of metallic materials under hydrogen-containing environments; S3: Construct a cohesive constitutive model and obtain the parameters of the cohesive constitutive model; S4: Conduct electron backscatter diffraction micro-characterization experiments on metallic materials to obtain microstructure characteristics and construct polycrystalline models; S5: Construct a crystal plastic constitutive model and obtain the crystal plastic constitutive model parameters; S6: Couple crystal plastic constitutive and cohesive constitutive, and use a trial-and-error method to calibrate the undetermined parameters of crystal plasticity; S7: Conduct finite element simulation analysis of hydrogen-induced cracking behavior with different microstructure characteristics under hydrogen-exposed environment to obtain stress-strain data and crack data.
[0006] Furthermore, step S1 specifically involves: preparing the metal material as a test sample according to the relevant requirements of the testing instrument for the test sample, and charging the metal sample with hydrogen at different hydrogen concentrations and conducting mechanical property tests to obtain the true stress-true strain data of the metal material at different hydrogen concentrations.
[0007] Furthermore, step S2 specifically involves: preparing the metal material as a test sample according to the relevant requirements of the testing instrument for the test sample, purging the metal sample with hydrogen at different hydrogen concentrations and conducting fracture toughness tests to obtain the stress intensity factor of the metal material at different hydrogen concentrations.
[0008] Furthermore, the cohesive constitutive model includes: Elastic phase ( ): ; In the formula: T i for i Directional traction force; K i for i Stiffness in the direction of motion; δ i for i Damage displacement in the direction; n , s , t These are the normal direction, the first shear direction, and the second shear direction, respectively. Damage stage ( ): ; ; In the formula: Di cohesive unit i Directional damage factor; This represents the maximum damage displacement. This represents the maximum equivalent damage displacement under the mixed cracking mode; for i Critical damage displacement in the direction.
[0009] Furthermore, the parameters of the cohesive constitutive model include the elastic modulus, Poisson's ratio, stiffness, fracture stress, and normal critical damage traction force of the metallic material.
[0010] Furthermore, step S4 specifically involves: characterizing the microstructure of the metallic material using a scanning electron microscope equipped with EBSD; analyzing and processing the observation data using analysis software to obtain crystal characteristic parameters; and establishing a polycrystalline model that conforms to the microstructure characteristics of the metallic material based on the obtained EBSD observation data of the metallic material.
[0011] Furthermore, the crystal plastic constitutive model includes: Kinematic model: ; In the formula: F This represents the total deformation gradient; F p This represents the plastic deformation gradient caused by dislocation slip. F e The elastic deformation gradient caused by lattice elongation and rotation; Slip model: ; In the formula: Let α be the shear strain rate of the slip system α; Reference shear strain rate; Let be the partial shear stress of the slip system α; For slip system α Deformation resistance; n The strain rate sensitivity coefficient; Voce hardening model: ; In the formula: h αβ Hardening modulus; q αβ For potential hardening matrix; h 0 represents the initial hardening modulus; For slip system β The critical shear stress; This represents the saturated shear stress. a This is the hardening index.
[0012] Furthermore, the parameters of the crystal plastic constitutive model include the initial values of the elastic and plastic parameters of the metallic material.
[0013] Further, step S6 specifically involves: compiling the crystal plastic constitutive model and the cohesive constitutive model; embedding cohesive elements into the polycrystalline model; assigning the polycrystalline model a crystal plastic constitutive model and the cohesive elements a cohesive constitutive model, thereby achieving coupling between the crystal plastic constitutive model and the cohesive constitutive model; subsequently assigning the polycrystalline model crystal orientation, crystal plastic constitutive parameters, and cohesive constitutive parameters, and applying corresponding displacement constraints and displacement loads to the model boundary while keeping the elastic parameters unchanged; setting a set of gradient values for each obtained initial plastic parameter; and calibrating the plastic parameters one by one using a trial-and-error method.
[0014] Furthermore, the different microstructure characteristics include one or more of the following: grain boundary angle, grain size, type, distribution location, and size of microdefects; the stress-strain data and crack data include one or more of the following: stress-strain curve, stress contour map, displacement contour map, crack initiation location, propagation path, and propagation rate.
[0015] The beneficial effects of this invention are as follows: This invention achieves high-precision simulation of the microscopic mechanism of hydrogen-induced cracking in metallic materials under hydrogen-exposed environments by coupling crystal plasticity models and cohesive force models and combining multi-source experimental data.
[0016] Based on the true stress-true strain curves obtained from hydrogen-charged mechanical property tests, the stress intensity factor obtained from fracture toughness tests, and the crystal characteristic parameters from EBSD microscopic characterization, this invention constructs a polycrystalline model that reflects the true response of the material. The crystal plasticity model accurately describes the dislocation slip and plastic deformation mechanism within the grains, while the cohesive force model quantitatively describes the evolution process of hydrogen-induced grain boundary damage. The two can work together to reveal the influence of microstructure characteristics such as grain boundary angle and defect distribution on the crack initiation location, propagation path, and rate.
[0017] This invention calibrates crystal plasticity parameters through a trial-and-error method and, based on fracture energy theory, [determines / determines] the plasticity parameters of crystals. K IC The derivation of cohesive parameters significantly reduces model uncertainty and ensures that simulation results and experimental errors are controllable. This method can quantitatively analyze the interaction mechanism of hydrogen concentration, microstructure, and cracking behavior, providing an effective solution that combines theoretical rigor and engineering practicality for the hydrogen embrittlement resistance design and safety assessment of hydrogen-contaminated equipment materials. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0019] Figure 1 This is a flowchart of the present invention; Figure 2 The true stress-true strain curve of X80 pipe steel at a hydrogen concentration of 5% is shown. Figure 3 This is a schematic diagram of the bilinear cohesive constitutive model. Figure 4 This is a diagram showing the grain orientation and size distribution; Figure 5 This is a schematic diagram of a polycrystalline finite element model of a metallic material. Figure 6 This is a schematic diagram of the boundary conditions for a polycrystalline finite element model of a metallic material. Figure 7 A comparison chart of true stress-true strain curves from finite element simulation and experiment; Figure 8 Stress contour plots and crack propagation paths along grains for models under different strain variables; Figure 9 Schematic diagram of polycrystalline finite element models with different grain sizes; Figure 10 The true stress-true strain curves are for different grain sizes. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.
[0021] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0022] The following detailed description of some embodiments of the present invention is provided in conjunction with the accompanying drawings. Unless otherwise specified, the following embodiments and features can be combined with each other.
[0023] See Figure 1A method for simulating hydrogen-induced cracking based on an experimental model of crystal plasticity and cohesion, which mainly includes the following steps: Step S1: Conduct hydrogen-charged mechanical property tests on the metallic materials to obtain the true stress-true strain curves of the metallic materials under hydrogen immersion conditions. In this embodiment, the mechanical property parameters of X80 pipe steel are obtained by in-situ hydrogen-charged slow strain rate tensile tests. The metallic material is prepared as the test sample according to the requirements of the testing instrument regarding the shape, size, surface roughness, and other relevant aspects. The test environment is set at a temperature of 25℃, a total pressure of 10MPa, and a strain rate of 10... -6 / s. The gas composition is nitrogen and hydrogen, with nitrogen at 9.5 MPa and hydrogen at 0.5 MPa. True stress-true strain data for the metallic material at a hydrogen concentration of 5% are obtained as follows: Figure 2 As shown.
[0024] Step S2: Conduct hydrogen-charged fracture toughness tests on metallic materials to obtain the stress intensity factor of the metallic materials under hydrogen-bearing conditions. K IC This embodiment uses in-situ hydrogen-charged fracture toughness testing to obtain the stress intensity factor of X80 pipe steel. K IC According to the requirements of the testing instrument regarding the shape, size, surface roughness, and other relevant aspects of the test sample, the metallic material was prepared as the test sample, and fatigue cracks were pre-induced. The test environment was set at a temperature of 25℃, a total pressure of 10MPa, and a strain rate of 10. -6 / s. The gas composition is nitrogen and hydrogen, with nitrogen at 9.5 MPa and hydrogen at 0.5 MPa. Obtain the stress intensity factor of the metallic material at a hydrogen concentration of 5%. K IC .
[0025] Step S3: Construct a cohesive constitutive model and obtain the constitutive model parameters. In this embodiment, the following parameters are selected: Figure 3 The bilinear cohesive constitutive model shown is used to describe the hydrogen-induced damage and cracking behavior of grain boundaries in metallic materials under hydrogen-exposed environments. This constitutive model divides grain boundary damage into three stages: elastic stage, damage stage, and free surface stage. The constitutive relations of each stage are shown in the following equations: Elastic phase ( ): ; In the formula: T i for i Directional traction force; K i for i Stiffness in the direction of motion; δ i for i Damage displacement in the direction; for iCritical damage displacement in the direction.
[0026] Damage stage ( ): ; ; In the formula: D i cohesive unit i Directional damage factor; This represents the maximum damage displacement. This represents the maximum equivalent damage displacement under the mixed cracking mode.
[0027] Free surface ( ): .
[0028] Damage initiation criteria (one of them): Maximum nominal stress criterion: ; .
[0029] Maximum nominal strain criterion: ; In the formula: ε In response to the situation; ε max The critical damage strain is denoted as .
[0030] Quadratic stress criterion: .
[0031] Quadratic strain criterion: .
[0032] Displacement-based damage evolution criteria: ; In the formula: δ fail This represents the effective displacement when the damage is complete.
[0033] Energy-based damage evolution criteria: ; In the formula: for i Fracture energy in the direction of fracture; for i Critical fracture energy in the direction; λ is a power exponent used to describe the damage evolution of grain boundaries under mixed cracking modes.
[0034] In this embodiment, the quadratic stress criterion is selected as the damage initiation criterion for the cohesive element: ; In this embodiment, an energy-based damage evolution criterion is selected: ; The acquisition of constitutive model parameters includes: calculating the elastic modulus of metallic materials from true stress-true strain data. E、 Poisson's ratio ν Stiffness K i Fracture stress σ f Normal critical damage traction force ; in, ; ; ; ; From stress intensity factor K IC Calculate the normal critical fracture energy : ; .
[0035] The values of the undetermined parameters for the selected bilinear cohesive constitutive model are shown in Table 1: Table 1 Constitutive parameters of bilinear cohesion
[0036] Step S4: Conduct electron backscatter diffraction microscopic characterization experiments on metallic materials to obtain microstructure characteristics and construct a polycrystalline model.
[0037] In this embodiment, the metallic material is prepared as a test sample according to the requirements of the testing instrument regarding the shape, size, surface roughness, and other relevant aspects of the test sample. The microstructure of the metallic material is observed using a scanning electron microscope equipped with EBSD, and the observation data is analyzed and processed using OIM Analysis software to obtain... Figure 4 (a) shows the grain orientation distribution diagram and as shown in the figure. Figure 4(b) shows the crystal size distribution. Based on the acquired EBSD observation data of metallic materials, a quasi-three-dimensional polycrystalline model was established using Neper modeling software to simulate the hydrogen-induced crack propagation behavior of X80 pipe steel. The number of grains and units contained in the polycrystalline model plays an important role in the macroscopic and microscopic mechanical response of metallic materials. By establishing models with different numbers of grains and units for simulation verification, it was found that the polycrystalline model divided into 8000 units, containing more than 100 grains, can more accurately characterize the macroscopic and microscopic mechanical statistical results of metallic materials. The polycrystalline model is shown below. Figure 5 As shown, the three-dimensional model has dimensions of 100 μm × 100 μm × 0.5 μm and contains a total of 350 grains.
[0038] Step S5: Construct a crystal plastic constitutive model and obtain initial constitutive model parameters. In this embodiment, a crystal plastic constitutive model based on phenomenological theory is adopted. This constitutive model mainly consists of a kinematic model, a slip model, and a Voce hardening model. The constitutive models of each part are shown in the following equations: Kinematic model: ; ; ; In the formula: F This represents the total deformation gradient; F p This represents the plastic deformation gradient caused by dislocation slip. F e The elastic deformation gradient caused by lattice elongation and rotation; J This represents the volume change ratio of the crystal. D For symmetric elongation or deformation rate tensors; Ω For antisymmetric rotation tensors; L p This represents the plastic velocity gradient; L e The elastic velocity gradient; For slip system α shear strain rate; s α The slip direction vector; n α This is the direction vector of the normal to the slip surface.
[0039] Slip model: ; ; ; In the formula: Reference shear strain rate; Let be the partial shear stress of the slip system α; For slip system α Deformation resistance; It is lattice friction; For slip system α The critical shear stress. n The strain rate sensitivity coefficient; For slip system β shear strain rate; h αβ This is the hardening modulus.
[0040] Voce hardening model: ; In the formula: q αβ For potential hardening matrix; h 0 represents the initial hardening modulus; For slip system β The critical shear stress; This represents the saturated shear stress. a This is the hardening index.
[0041] In this embodiment, the parameters of the initial constitutive model to be determined for X80 pipe steel were obtained by consulting existing literature, as shown in Table 2: Table 2 Constitutive parameters of crystal plasticity (before calibration)
[0042] Step S6: Couple the crystal plastic constitutive model with the cohesive constitutive model, and use a trial-and-error method to calibrate the undetermined parameters of crystal plasticity.
[0043] In this embodiment, Abaqus finite element software was selected as the simulation software. Based on the Abaqus user subroutine UMAT and user-defined element UEL, the crystal plasticity constitutive model and the cohesive constitutive model were compiled using Fortran language. Cohesive elements were embedded in the finite element mesh model to couple the crystal plasticity constitutive model and the cohesive constitutive model. Subsequently, the polycrystalline model established by Neper software was imported into Abaqus software, and the polycrystalline model was divided using eight-node hexahedral solid elements (C3D8), containing a total of 97336 C3D8 elements. 350 sets of crystal orientation parameters, initial crystal plasticity constitutive parameters, and cohesive constitutive parameters extracted from EBSD data were assigned to the polycrystalline model. The displacements in the y-direction at the bottom of the model, the x-direction at the left end, and the z-direction at the back were restricted, and a displacement load along the y-direction was applied above the model, such as... Figure 6 As shown.
[0044] In this embodiment, a trial-and-error method is used. , n, h0、、 , a Five crystal plasticity parameters were calibrated. First, lattice friction was selected. Five sets of values (40, 50, 60, 70, and 80) were set up as trial and error targets. Simulation calculations were performed while keeping other constitutive parameters constant. True stress-true strain curves for different values were obtained and compared with experimentally obtained true stress-true strain curves. The value that best matched the experimental results was selected as the lattice friction force. The calibration values were then used to calibrate the remaining four crystal plastic constitutive parameters in sequence, using the same calibration method. The final calibration results are as follows: Figure 7 As shown in Table 3, the calibrated crystal plastic constitutive parameters are as follows.
[0045] Table 3 Constitutive parameters of crystal plasticity (after calibration)
[0046] Step S7: Perform finite element simulation analysis of hydrogen-induced cracking behavior under different microstructure characteristics in a hydrogen-exposed environment to obtain stress-strain data and crack data. In this embodiment, finite element simulation analysis of hydrogen-induced cracking behavior under different microstructure characteristics is performed using grain size as an example.
[0047] (1) Stress cloud diagram and crack propagation path analysis of a model with 350 grains at a hydrogen concentration of 5% Figure 8 The figures show stress contour plots and crack propagation paths of a model under different strain values after microcrack initiation. Arrows indicate the crack propagation direction, and dashed boxes represent stress concentration areas at the crack tip. As can be seen, after crack initiation at the grain boundary, the crack propagates bidirectionally along the grain boundary as the strain continues to increase. When it propagates to the polygrain junction, the crack tends to continue propagating along the high-stress grain boundary because the grain boundary damage is more severe in the high-stress region. Furthermore, as... Figure 8 As shown in (b), (c), and (d), new cracks initiate, propagate, and merge with the original crack in the uninitiated region at the leading edge of the original crack, forming a fracture path. The internal stress within the grains on both sides of the path is released and decreases, while significant stress concentration still exists at the crack tip, providing a potential path for crack propagation. Therefore, the propagation behavior of intergranular cracks in the microstructure mainly includes three stages: initiation, propagation, and merging, gradually forming large cracks that lead to material failure through the merging of local microcracks.
[0048] (2) Analysis of true stress-true strain curves of polycrystalline models with different grain sizes at a hydrogen concentration of 5% like Figure 9As shown in (a), (b), and (c), to investigate the influence of grain size on the crack propagation behavior of X80 pipe steel, three polycrystalline models containing 350, 250, and 150 grains respectively were established in a 100 μm × 100 μm × 0.5 μm cube for numerical simulation analysis. Figure 10 As shown, in the elastic stage, the yield strength of the model gradually decreases with the increase of the average grain size. However, upon entering the plastic deformation stage, the ultimate tensile strength also decreases with the increase of the average grain size, a trend consistent with the Hall-Petch effect. Figure 10 It can be seen that, compared with the model with 150 grains, the crack initiation strain of the models with 250 and 350 grains increased from 0.0283 to 0.0361 and 0.0487, respectively, representing increases of 27.6% and 72.1%. Similarly, the ultimate tensile strength increased from 615.28 MPa to 633.49 MPa and 667.27 MPa, respectively, representing increases of 3.0% and 8.4%. This indicates that cracks are more likely to initiate at locations with larger average grain sizes and propagate at an extremely rapid rate until the model fractures.
[0049] This invention achieves high-precision simulation of the microscopic mechanism of hydrogen-induced cracking in metallic materials under hydrogen-containing environments by coupling a crystal plasticity model and a cohesive force model, combined with multi-source experimental data. Based on true stress-true strain curves obtained from hydrogen-charged mechanical property tests, stress intensity factors obtained from fracture toughness tests, and crystal characteristic parameters from EBSD microscopic characterization, a polycrystalline model reflecting the material's true response is constructed. The crystal plasticity model accurately characterizes the dislocation slip and plastic deformation mechanisms within grains, while the cohesive force model quantitatively describes the evolution process of hydrogen-induced grain boundary damage. Together, they can reveal the influence of microstructural features such as grain boundary angles and defect distribution on crack initiation location, propagation path, and rate. Crystal plasticity parameters are calibrated using a trial-and-error method, and the simulation is based on fracture energy theory. K IC The derivation of cohesive parameters significantly reduces model uncertainty, ensuring that simulation results and experimental errors are controllable. This method can quantitatively analyze the interaction mechanism of hydrogen concentration, microstructure, and cracking behavior, providing an effective solution with both theoretical rigor and engineering practicality for the hydrogen embrittlement resistance design and safety assessment of materials for hydrogen-contaminated equipment.
[0050] For the foregoing embodiments, in order to simplify the description, they are all described as a series of actions. However, those skilled in the art should understand that this application is not limited to the described order of actions, because according to this application, some steps can be performed in other orders or simultaneously. Furthermore, those skilled in the art should also understand that the embodiments described in the specification are preferred embodiments, and the actions involved are not necessarily essential to this application.
[0051] The above embodiments describe the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Modifications and variations made by those skilled in the art without departing from the spirit and scope of the invention should be within the protection scope of the appended claims.
Claims
1. A method for simulating hydrogen-induced cracking based on an experimental model coupling crystal plasticity and cohesion, characterized in that, Includes the following steps: S1: Conduct hydrogen-charged mechanical property tests on metallic materials to obtain true stress-strain curves of metallic materials under hydrogen-exposed environments; S2: Conduct hydrogen-charged fracture toughness tests on metallic materials to obtain the stress intensity factor of metallic materials under hydrogen-containing environments; S3: Construct a cohesive constitutive model and obtain the parameters of the cohesive constitutive model; S4: Conduct electron backscatter diffraction micro-characterization experiments on metallic materials to obtain microstructure characteristics and construct polycrystalline models; S5: Construct a crystal plastic constitutive model and obtain the crystal plastic constitutive model parameters; S6: Couple crystal plastic constitutive and cohesive constitutive, and use a trial-and-error method to calibrate the undetermined parameters of crystal plasticity; S7: Conduct finite element simulation analysis of hydrogen-induced cracking behavior with different microstructure characteristics under hydrogen-exposed environment to obtain stress-strain data and crack data.
2. The experimental-based method for simulating hydrogen-induced cracking by coupling a crystal plasticity and cohesion model as described in claim 1, characterized in that... Step S1 specifically involves: preparing the metal material as the test sample according to the relevant requirements of the testing instrument for the test sample, purging the metal sample with hydrogen at different hydrogen concentrations and conducting mechanical property tests to obtain the true stress-true strain data of the metal material at different hydrogen concentrations.
3. The experimental-based method for simulating hydrogen-induced cracking by coupling a crystal plasticity and cohesion model as described in claim 1, characterized in that... Step S2 specifically involves: preparing the metal material as a test sample according to the relevant requirements of the testing instrument for the test sample, purging the metal sample with hydrogen at different hydrogen concentrations and conducting fracture toughness tests to obtain the stress intensity factor of the metal material at different hydrogen concentrations.
4. The experimental-based method for simulating hydrogen-induced cracking by coupling a crystal plasticity and cohesion model as described in claim 1, characterized in that... The cohesive constitutive model includes: Elastic phase ( ): ; In the formula: T i for i Directional traction force; K i for i Stiffness in the direction of motion; δ i for i Damage displacement in the direction; n , s , t These are the normal direction, the first shear direction, and the second shear direction, respectively. Damage stage ( ): ; ; In the formula: D i cohesive unit i Directional damage factor; This represents the maximum damage displacement; This represents the maximum equivalent damage displacement under the mixed cracking mode; for i Critical damage displacement in the direction.
5. The experimental-based method for simulating hydrogen-induced cracking by coupling a crystal plasticity and cohesion model as described in claim 1, characterized in that... The parameters of the cohesive constitutive model include the elastic modulus, Poisson's ratio, stiffness, fracture stress, and normal critical damage traction force of the metallic material.
6. The experimental-based method for simulating hydrogen-induced cracking by coupling a crystal plasticity and cohesion model as described in claim 1, characterized in that, Step S4 specifically involves: characterizing the microstructure of the metallic material using a scanning electron microscope equipped with EBSD; analyzing and processing the observation data using analysis software to obtain crystal characteristic parameters; and establishing a polycrystalline model that conforms to the microstructure characteristics of the metallic material based on the obtained EBSD observation data.
7. The experimental-based method for simulating hydrogen-induced cracking by coupling a crystal plasticity and cohesion model as described in claim 1, characterized in that... The crystal plastic constitutive model includes: Kinematic model: ; In the formula: F This represents the total deformation gradient; F p This represents the plastic deformation gradient caused by dislocation slip. F e The elastic deformation gradient caused by lattice elongation and rotation; Slip model: ; In the formula: Let α be the shear strain rate of the slip system α; Reference shear strain rate; Let be the partial shear stress of the slip system α; For slip system α Deformation resistance; n The strain rate sensitivity coefficient; Voce hardening model: ; In the formula: h αβ Hardening modulus; q αβ For potential hardening matrix; h 0 represents the initial hardening modulus; For slip system β The critical shear stress; This represents the saturated shear stress. a This is the hardening index.
8. The experimental-based method for simulating hydrogen-induced cracking by coupling a crystal plasticity and cohesion model as described in claim 1, characterized in that... The parameters of the crystal plastic constitutive model include the initial values of the elastic and plastic parameters of the metallic material.
9. The experimental-based method for simulating hydrogen-induced cracking by coupling a crystal plasticity and cohesion model as described in claim 1, characterized in that... Step S6 specifically involves: compiling the crystal plastic constitutive model and the cohesive constitutive model; embedding cohesive elements into the polycrystalline model; assigning the polycrystalline model a crystal plastic constitutive model and the cohesive elements a cohesive constitutive model, thereby achieving coupling between the crystal plastic constitutive model and the cohesive constitutive model; subsequently assigning crystal orientation, crystal plastic constitutive parameters, and cohesive constitutive parameters to the polycrystalline model; applying corresponding displacement constraints and displacement loads to the model boundary while keeping the elastic parameters unchanged; setting a set of gradient values for each obtained initial plastic parameter; and calibrating the plastic parameters one by one using a trial-and-error method.
10. The experimental-based method for simulating hydrogen-induced cracking by coupling a crystal plasticity and cohesion model as described in claim 1, characterized in that... The different microstructure features include one or more of the following: grain boundary angle, grain size, type, distribution location and size of microdefects; The stress-strain data and crack data include one or more of the following: stress-strain curves, stress contour maps, displacement contour maps, crack initiation locations, propagation paths, and propagation rates.
Citation Information
Cited By
Molecular dynamics-cohesion cross-scale simulation method for hydrogen induced cracking
CN121237237A
A hydrogen induced cracking molecular dynamics-cohesion multiscale simulation method
CN121237237B